Correlates of Obstetric Risk Perception and Recognition of Danger Signs in Kano, Northern Nigeria - Zubairu Iliyasu; Hadiza S. Galadanci; Abubakar Abdurrahim; Abubakar Jibo; Hamisu M. Salihu; Muktar H. Aliyu (Ubiquity Press, 2019)
Background: Risk perception and recognition of danger signs are important cues for accessing obstetric care. These measures are not well documented in many resource-limited settings, including northern Nigeria, a region with poor maternal health indices. Objective: To assess community level obstetric risk perception, danger sign recognition and their predictors in Kano, northern Nigeria. Method: This is a community-based cross-sectional study. Participants were surveyed using structured, pretested questionnaires. Knowledge of obstetric risk factors and danger sign recognition were analyzed, and their predictors modeled using logistic regression to generate adjusted odds ratios (AORs). Results: The obstetric risk factors identified by the 400 respondents included: maternal age (64.3%), history of abortion (37.0%), postpartum haemorrhage (36.0%), previous operative delivery (31.8%), and high parity (31.3%). The most frequently recognised danger signs during pregnancy were: vaginal bleeding (76.8%), seizures (44.5%), and severe abdominal pain (34.8%). Common intrapartum danger signs recognised included: severe bleeding (77.8%), seizures (55.5%), and loss of consciousness (38.3%). Severe bleeding (80.5%), seizures (42.0%), and high fever (28.5%) were the top three danger signs identified in the postpartum period. At multivariate level, respondent sex (female vs. male) (aOR = 3.10, 95% CI = 1.67-5.74), ethnicity (Yoruba vs. Hausa) (aOR = 7.53, 95% CI = 2.51-22.6), occupation (employed vs. unemployed) (aOR = 4.07, 95% CI = 1.87-8.84) and parity (≥5 versus 0) (aOR = 0.23, 95% CI = 0.06-0.92) predicted good obstetric risk perception. Participants' ethnicity (Yoruba vs. Hausa) (aOR = 4.40, 95% CI = 1.10-19.2) and obstetric risk perception (good vs. poor) (aOR = 12.0, 95% CI = 6.8-21.2) predicted danger sign recognition. Conclusion: The perception of obstetric risk and recognition of danger signs were influenced by participant sex, parity, employment status, and ethnicity. Targeted communication strategies and community-based education are essential to enhance effective utilisation of emergency obstetric services.